1991
DOI: 10.1007/bf01613283
|View full text |Cite
|
Sign up to set email alerts
|

Pineal melatonin inhibition of tumor promotion in theN-nitroso-N-methylurea model of mammary carcinogenesis: potential involvement of antiestrogenic mechanisms in vivo

Abstract: The N-methyl-N-nitrosourea (NMU) model of hormone-responsive rat mammary carcinogenesis was used to address the hypothesis that melatonin (Mel), the principle hormone of the pineal gland, inhibits tumorigenesis by acting as an anti-promoting rather than an anti-initiating agent. Daily late-afternoon injections of Mel (500 micrograms/day), restricted to the initiation phase of NMU mammary tumorigenesis, were ineffective in altering tumor growth over a 20-week period. When Mel treatment was delayed for 4 weeks a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
0
2

Year Published

1995
1995
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(48 citation statements)
references
References 26 publications
2
44
0
2
Order By: Relevance
“…Presuming that melatonin has a real anticarcinogenic property, the breast-cancer-specific decrease may point to a mechanism with an intermediary role for oestrogens (Blask et al, 1991;Baldwin and Barret, 1998) in the biophysical/chemical pathway from visible light to endogenous melatonin secretion and, finally, to the development of breast cancer. It is pertinent, however, that it is not known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presuming that melatonin has a real anticarcinogenic property, the breast-cancer-specific decrease may point to a mechanism with an intermediary role for oestrogens (Blask et al, 1991;Baldwin and Barret, 1998) in the biophysical/chemical pathway from visible light to endogenous melatonin secretion and, finally, to the development of breast cancer. It is pertinent, however, that it is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin may possess anticarcinogenic properties (Blask et al, 1991), so that increased exposures to light-at-night may decrease nocturnal melatonin secrection and thus contribute to the observed increases in breast cancer incidence rates (Stevens, 1987). It has been reasoned that women who are profoundly blind, and therefore not susceptible to light-at-night, should have a reduced risk of breast cancer compared with those with intact vision (Hahn, 1991).…”
mentioning
confidence: 99%
“…In particular, melatonin injection has been reported to inhibit chemically induced mammary tumor development in rats, and pinealectomy enhances it in both the DMBA model (35) and the N-nitroso-N-methylurea (NMU) model (36). There are several mechanistic interpretations of these observations (37).…”
Section: Melatonin and Breast Cancermentioning
confidence: 99%
“…The apoptotic effect of this sequential treatment with melatonin and atRA appears to be both cell and regimen specific as (a) ER-negative MDA-MB-231 and BT-20 breast tumour cells were unaffected, and (b) the simultaneous administration of melatonin and atRA was not associated with apoptosis in any of the breast cancer cell lines studied. Taken together, the results suggest that use of an appropriate regimen of melatonin and atRA should be considered for preclinical and clinical evaluation against ER-positive human breast cancer.Keywords: apoptosis; melatonin; retinoic acid; MCF-7; breast cancer Melatonin, the major hormonal product of the pineal gland, has repeatedly been shown to exert a negative growth-regulatory influence on the development and growth of hormone-responsive breast cancer (Blask et al, 1986(Blask et al, , 1991. In addition, our laboratory (Hill and Blask, 1988) as well as others (Cos and Sanchez-Barcel6, 1994) have shown that melatonin treatment can act directly on hormoneresponsive human breast cancer cells in vitro to suppress their proliferation.…”
mentioning
confidence: 98%
“…Keywords: apoptosis; melatonin; retinoic acid; MCF-7; breast cancer Melatonin, the major hormonal product of the pineal gland, has repeatedly been shown to exert a negative growth-regulatory influence on the development and growth of hormone-responsive breast cancer (Blask et al, 1986(Blask et al, , 1991. In addition, our laboratory (Hill and Blask, 1988) as well as others (Cos and Sanchez-Barcel6, 1994) have shown that melatonin treatment can act directly on hormoneresponsive human breast cancer cells in vitro to suppress their proliferation.…”
mentioning
confidence: 98%